The Effect of Load Punch in the Limits of Strain paths for (1006) Steel Sheets by using Stretch Forming - Obeed Balod, Anas (Anbar Journal of Engineering Sciences, 2012)
To control on the operation of sheet metal forming without failure, A diagram is used in which the range accepted, failure and critical deformation range are shown. This diagram is known as the Forming limit diagram. It is considered as one of the important tool to determine the formability of sheet metals. Every sheet metal has its own forming limit diagram which determines its formability, strain limit and the forming regions. In this paper, the forming limit diagrams (FLDs) were experimentally evaluated for low carbon steel sheets with different thickness (0.6, 0.75, 0.85, 1.2mm). The highest limit strain in the forming limit diagram is found in the steel sheet at thickness (1.2mm) and the lowest limits in the steel sheet at (0.6mm), this meaning that the formability improve with increase the thickness of steel sheet. The effect of load punch is higher at biaxial stretch path and the lowest at uniaxial tension path. The load punch is change with different thickness of sheet at the same path. The maximum thinning is found in the biaxial stretch path and the lowest of thinning in plane strain path for all sheets.